Opioid-receptor (OR) signaling cascades in rat cerebral cortex and model cell lines: the role of plasma membrane structure - Ujčíková, Hana; Brejchová, Jana; Vošahlíková, Miroslava; Kagan, Dmytro; Dlouhá, Kateřina; Sýkora, Jan; Merta, Ladislav; Drastichová, Zdeňka; Novotný, Jiří; Ostašov, Pavel; Roubalová, Lenka; Parenti, M; et al. (Physiological research, 2014)
Large number of extracellular signals is received by plasma membrane receptors which, upon activation, transduce information into the target cell interior via trimeric G-proteins (GPCRs) and induce activation or inhibition of adenylyl cyclase enzyme activity (AC). Receptors for opioid drugs such as morphine (micro-OR, delta-OR and kappa-OR) belong to rhodopsin family of GPCRs. Our recent results indicated a specific up-regulation of AC I (8-fold) and AC II (2.5-fold) in plasma membranes (PM) isolated from rat brain cortex exposed to increasing doses of morphine (10-50 mg/kg) for 10 days. Increase of ACI and ACII represented the specific effect as the amount of ACIII-ACIX, prototypical PM marker Na, K-ATPase and trimeric G-protein alpha and beta subunits was unchanged. The up-regulation of ACI and ACII faded away after 20 days since the last dose of morphine. Proteomic analysis of these PM indicated that the brain cortex of morphine-treated animals cannot be regarded as being adapted to this drug because significant up-regulation of proteins functionally related to oxidative stress and alteration of brain energy metabolism occurred. The number of delta-OR was increased 2-fold and their sensitivity to monovalent cations was altered. Characterization of delta-OR-G-protein coupling in model HEK293 cell line indicated high ability of lithium to support affinity of delta-OR response to agonist stimulation. Our studies of PM structure and function in context with desensitization of GPCRs action were extended by data indicating participation of cholesterol-enriched membrane domains in agonist-specific internalization of delta-OR. In HEK293 cells stably expressing delta-OR-G(i)1alpha fusion protein, depletion of PM cholesterol was associated with the decrease in affinity of G-protein response to agonist stimulation, whereas maximum response was unchanged. Hydrophobic interior of isolated PM became more "fluid", chaotically organized and accessible to water molecules. Validity of this conclusion was supported by the analysis of an immediate PM environment of cholesterol molecules in living delta-OR-G(i)1alpha-HEK293 cells by fluorescent probes 22- and 25-NBD-cholesterol. The alteration of plasma membrane structure by cholesterol depletion made the membrane more hydrated. Understanding of the positive and negative feedback regulatory loops among different OR-initiated signaling cascades (micro-, delta-, and kappa-OR) is crucial for understanding of the long-term mechanisms of drug addiction as the decrease in functional activity of micro-OR may be compensated by increase of delta-OR and/or kappa-OR signaling.
Keywords: Receptors, Opioid; HEK293 buňky; Structure-Activity Relationship; signální transdukce; Analgesics, Opioid; mozková kůra; HEK293 Cells; opioidní analgetika; Signal Transduction; Membrane Lipids; vztahy mezi strukturou a aktivitou; krysa rodu Rattus; Cell Membrane; Animals; lidé; fluidita membrány; Humans; zvířata; receptory opiátové; buněčná membrána; Rats; Membrane Fluidity; membránové lipidy; Cerebral Cortex